A novel XbaI multiplex PCR method for rapid typing of Klebsiella pneumoniae strains - Ibrahim Ali Al-Zahrani (Scientific Reports)
Abstract This study focused on exploiting single-nucleotide polymorphism (SNP) variations in and around XbaI-restriction sites (5′….T↓CTAGA….3′) within the genomes of Klebsiella pneumoniae to develop a multiplex PCR genotyping technique that integrates the high discrimination of pulsed-field gel electrophoresis (PFGE) with the straightforwardness of a multiplex PCR-based procedure, for routine use in clinical laboratories. The XbaI-multiplex PCR method was evaluated in silico using 10 reference strains and subsequently compared to PFGE and MLST, revealing similar clustering patterns of test strains in most cases. Furthermore, 29 clinical isolates with known sequence types (STs) were analysed ed using XbaI-multiplex PCR, which demonstrated acceptable discriminative ability and relative concordance with MLST results. Like other PCR-based typing methods, the XbaI-multiplex PCR method is not only cost-effective but also user-friendly as it does not necessitate the use of complex instruments or specialized skills, and results are available within 4–6 h. Its implementation relies on standard clinical laboratory instruments, such as a PCR machine and agarose gel electrophoresis. However, the XbaI-multiplex PCR still requires further evaluations with a larger number of clinical isolates, including K. pneumoniae isolates obtained from hospital outbreaks.